Hydroxyapatite/Cerium Oxide Composites: Sintering, Microstructural, Mechanical and In-vitro Bioactivity Properties - PAZARLIOĞLU, SÜLEYMAN SERDAR (My University, 2019)
In the present study, the effects of cerium oxide (CeO2) additive on the sinterability, microstructural, mechanical and in-vitro bioactivityproperties of a commercially synthetic hydroxyapatite (HA) was investigated. HA without CeO2 additive started to decompose at 1100oC, but the decomposition temperature of the CeO2 added samples decreased up to 900 oC. Decomposition rate of the sintered samples increasedby increasing sintering temperature. It was about 5.8% for pure HA, and increased to 11.4% when the CeO2 additive to HA reachedto 2.5 wt%. SEM images showed that an excessive grain growth as well as microcracks occured on the surface of pure HA when it wassintered at the temperatures than that of 1100 oC. The microcracks were also observed on the surface of HA-CeO2 composites, when theywere sintered at 1300 oC. The composite of HA-0.5CeO2 sintered at 1100 oC possess the higher fracture toughness (Kıc) (2.510 ± 0.225MPam-1/2) and the higher compressive strength (152.73 ± 6.31 MPa) compared to other HA-CeO2 composites, and its mechanical propertiesare higher than that of pure HA at about 2-3 times. In-vitro bioactivity test results showed that apatite layers on the surface of the sampleswere in the different morphologies.

Bu çalışmada, seryum oksit (CeO2) ilavesinin ticari saflıktaki bir sentetik hidroksiapatitin (HA) sinterlenebilme, mikroyapısal, mekanik ve in-vitro biyoaktivite özelliklerine etkileri incelenmiştir. CeO2 ilavesiz HA 1100 oC sıcaklıkta dekompoze olmaya başlamış, CeO2 ilave edilmiş numunelerde dekompoze olma sıcaklığı ise 900 oC’ ye kadar düşmüştür. Sinterlenmiş numunelerin dekompoze olma oranı sinterleme sıcaklığının artmasıyla artmıştır. Saf HA’ nın dekompoze olma oranı yaklaşık % 5.8 iken, HA’ ya yapılan CeO2 katkı maddesi ağırlıkça% 2.5’ e ulaştığında %11.4’ e yükselmiştir. SEM görüntüleri 1100 oC’ nin üstündeki sıcaklıklarda sinterlenen saf HA’ nın yüzeyinde aşırı tane büyümelerinin yanı sıra mikroçatlakların meydana geldiğini göstermiştir. Mikroçatlaklar ayrıca HA-CeO2 kompozitlerinin yüzeyinde, 1300 oC sıcaklıkta sinterlendiklerinde gözlemlenmiştir. 1100 oC’ de sinterlenmiş HA-0.5CeO2 kompoziti, diğer HA-CeO2 kompozitlerine kıyasla daha yüksek kırılma tokluğu (Kıc) (2.510 ± 0.225 MPam-1/2) ve daha yüksek basma dayanımına (152.73 ± 6.31 MPa) sahiptir ve mekanik özellikleri saf HA’ dan yaklaşık 2-3 kat daha yüksektir. İn-vitro biyoaktivite testi sonuçları, numunelerin yüzeyindeki apatit katmanlarının farklı morfolojilerde olduğunu göstermiştir.
Hidroksiapatit/Seryum Oksit Kompozitleri: Sinterlenebilme, Mikroyapısal, Mekanik ve İn-vitro Biyoaktivite Özellikleri
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler